DIAGNOSTIC VALUE OF MULTI-SLICE CT SCAN FOR RENAL ANGIO- MYOLIPOMA DETECTION: A CASE REPORT - Kevin Wenardi (Berkala Ilmiah Kedokteran Duta Wacana, 2021)
Background: Angiomyolipoma (AML) is a rare solid benign tumor that occurs at many sites, more commonly in the kidney, which arises from either the renal pelvis or the sinus, also referred to as renal hamartoma. AML is composed of blood vessels, smooth muscle cells, and fat hence the name. They are seen 80-90% as isolated lesions that occur sporadically and seen 25-50% of patients with tuberous sclerosis. AML may hard to be distinguished from renal cell carcinoma because of its presentation as enlarged lump. Computed tomography may help to diagnose AML. To get a definite diagnosis of AML, excision and histopathological examination is recommended in symptomatic patients, especially to prevent rupture hemorrhage. Objective: The purpose of this study was to evaluate multi-slice computed tomography with contrast in a male patient aged 49 years with Angiomyolipoma Case description: We herein present a case of renal AML in a 49 years old male patient, who presented with left flank pain for ~1 year. He has no history of hematuria and dysuria and tuberous sclerosis. Multi-slice computed tomography with contrast demonstrates a hypodense inhomogenous mass measuring 11x9,3 cm in the upper pole of the left kidney, hypertrophy of the left kidney, and hump sign of left kidney. At the later date, the patient underwent total left nephrectomy at another hospital and the postoperative histopathological examination confirmed the lesion as an AML. Conclusion: Angiomyolipoma is a rare benign tumor which usually occurs in the kidney that can be confused with malignant tumor. Ultrasonography and computed tomography can help to diagnose AML. The symptomatic patient requires surgical intervention.